High‐Performance Strain of Lead‐Free Relaxor‐Ferroelectric Piezoceramics by the Morphotropic Phase Boundary Modification (Adv. Funct. Mater. 32/2022). (8th August 2022) - Li, Tangyuan; Liu, Chang; Shi, Peng; Liu, Xiao; Kang, Ruirui; Long, Changbai; Wu, Ming; Cheng, Shaodong; Mi, Shaobo; Xia, Yuanhua; Li, Linglong; Wang, Dong; et al.
Abstract : Lead‐Free Piezoceramics In article number 2202307, Linglong Li, Dong Wang, and Xiaojie Lou, and co‐workers report a computationally aided composition design for discovering high‐performance lead‐free perovskite piezomaterials. The obtained bismuth sodium titanate‐based relaxor‐ferroelectric ceramic demonstrates low‐hysteresis large strains over a wide range of temperatures, which holds great promise for practical applications of actuator devices operating at room to high temperatures.